Circ_0027885 sponges miR-203-3p to regulate RUNX2 expression and alleviates osteoporosis progression - Shuhua Fang; Dingwen Cao; Zhanpo Wu; Jie Chen; Yafei Huang; Ying Shen; Zengxin Gao (BMC Musculoskeletal Disorders, 2024)
Abstract Background Osteoporosis (OP) is a progressive metabolic disorder that is difficult to cure clinically. The molecular mechanisms of OP urgently need to be further examined. This study was designed to explore the potential function of circ_0027885 during osteogenic differentiation, as well as the systematic interactions among circ_0027885, miR-203-3p and runt-related transcription factor 2 (RUNX2). Methods Relative levels of circ_0027885, miR-203-3p and RUNX2 were analyzed with RT-qPCR and western blotting. Alizarin red staining was performed to detect the mineralization ability under the control of circ_0027885 and miR-203-3p. Dual-luciferase reporter gene assay was conducted to examine the combination among circ_0027885, miR-203-3p and RUNX2. Results Our research demonstrated that circ_0027885 was significantly increased during hBMSCs differentiation. Overexpression of circ_0027885 notably facilitated osteogenic differentiation and upregulated RUNX2 expression, while knockdown of circ_0027885 reversed the above results. Through prediction on bioinformatics analysis, miR-203-3p was the target binding circ_0027885, and RUNX2 was the potential target of miR-203-3p. Subsequently, these changes induced by the overexpression of circ_0027885 were reversed upon addition of miR-203-3p mimic. Conclusions Circ_0027885 could sponge miR-203-3p to regulate RUNX2 expression and alleviate osteoporosis progression.